Experimental study on crumb rubberised concrete (CRC) and reinforced CRC slabs under static and impact loads. Issue 4 (1st October 2020) - Li, Danda; Xiao, Jianzhuang; Zhuge, Yan; Mills, Julie E.; Senko, Henry; Ma, Xing
ABSTRACT: This paper addresses the structural performance of crumb rubberised concrete (CRC) and reinforced CRC slabs under static and low-velocity impact loads. An innovated setup was designed to investigate the impact of behaviour of concrete material based on the drop-weight test. The drop-weight velocities before and after impact were recorded through a laser system. Based on the velocity variation, the energy that was absorbed in concrete material during the test, which also was the impact resistance of the sample's failure section, had been calculated. CRC samples with rubber percentages varying from 0% to 20% were tested. Experimental results verified the advantages of using rubber on material impact behaviour. Finally, as a structural application, reinforced CRC slabs were tested under static and impact loads. Experimental results showed that CRC slabs exhibited superior post-cracking performance with member moment capacities comparable or even higher than that of reinforced traditional concrete (TC) slabs. It is believed that this unique phenomenon was due to zip-shaped cracking section along CRC slab width. At last, a series of impact tests were conducted and test results showed a significant reduction in the peak stress response in CRC slabs when compared with TC slabs.